1985
DOI: 10.1111/j.1432-1033.1985.tb09119.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adenylate cyclase of human platelets by phorbol ester

Abstract: The influence of the phorbol ester, 12-0-tetradecanoylphorbol 13-acetate (TPA), a direct activator of the Ca2 +-activated, phospholipid-dependent protein kinase (protein kinase C), was studied on regulation of human platelet adenylate cyclase. Intact platelets were pretreated with the phorbol ester and, thereafter, membranes were prepared and the regulation of the hormone-sensitive adenylate cyclase in these membranes was studied. The following data were obtained: The TPA treatment applied had apparently no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
4

Year Published

1987
1987
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(84 citation statements)
references
References 29 publications
10
70
4
Order By: Relevance
“…Epinephrine induced a dose-dependent inhibition of forskolin-stimulated adenylate cyclase activity (fig.2); the effect of epinephrine was blocked by 10gM yohimbine indicating the involvement of az-adrenoceptors (not shown). In agreement with the data of Jakobs et al [6], we observed that the effect of epinephrine was marked- ly reduced in membranes from TPA-treated platelets as compared to the controls, i.e. IOOpM epinephrine induced a 35-40070 inhibition of adenylate cyclase activity in control membranes whereas in membranes from TPA-treated platelets the same concentration of epinephrine induced only a 5-100/o inhibition ( fig.2).…”
Section: Methodssupporting
confidence: 92%
“…Epinephrine induced a dose-dependent inhibition of forskolin-stimulated adenylate cyclase activity (fig.2); the effect of epinephrine was blocked by 10gM yohimbine indicating the involvement of az-adrenoceptors (not shown). In agreement with the data of Jakobs et al [6], we observed that the effect of epinephrine was marked- ly reduced in membranes from TPA-treated platelets as compared to the controls, i.e. IOOpM epinephrine induced a 35-40070 inhibition of adenylate cyclase activity in control membranes whereas in membranes from TPA-treated platelets the same concentration of epinephrine induced only a 5-100/o inhibition ( fig.2).…”
Section: Methodssupporting
confidence: 92%
“…Similarly, we [5] and others [6] have shown that incubation of pure preparations of Gi and Go with a purified human insulin receptor preparation leads to the phosphorylation of ce-Gi. It has been suggested that phosphorylation of Gi by protein kinase C may lead to its inactivation as incubation of platelets with tumour promoting phorbol esters, which activate protein kinase C, blocked the ability of CeE-adrenoceptors to inhibit adenylate cyclase activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al (1985) found, with rat liver, that the release ofprotein kinase C in the activated form occurs through limited proteolysis of the plasma membrane by trypsin. Jakobs et al (1985) found, with the human platelet, an impairment of the hormone-sensitive inhibitory pathway, dependent on the inhibitory guanine nucleotide binding regulatory protein (Ni), by 12-0-tetradecanoylphorbor 13-acetate (TPA), an activator of protein kinase C. In their experiments, the adenylate cyclase inhibition not involving the Ni protein and the operation of the stimulatory pathway remained unchanged. Katada et al (1985) found the phosphorylation of Ni protein by TPA in association with the impairment of the inhibitory pathway.…”
Section: Discussionmentioning
confidence: 98%